Effect of mega railway projects on small and medium construction companies: Impact and problems - Nurul Atiqah, Ab Hakim; Farouk, A M; Saffuan, Wan Ahmad; Rahimi, A. Rahman (Penerbit UMP, 2024)
Railway mega-projects are typically enormous large-scale investment projects that require a long time to develop and build. However, compared to other types of transportation, the railway is a safe mode of land transportation. Therefore, development such as railway mega-projects positively impacts small and medium construction companies. This study aims to study the impact of railway mega-projects on small and medium construction companies and investigate the problems that small and medium construction companies experience involving railway mega-projects. This study used a qualitative method of open-ended interviews to collect data from small and medium construction companies. The collected data from twenty individuals were analyzed using the thematic analysis method. The results show that the challenges of mega railway projects are divided into technical and resources. Apart from that, job opportunities are the main factor contributing to the impact of mega railway projects. The study contributes by providing insights on the impact of mega railway projects on small and medium construction companies and the challenges involving mega railway projects.